Subjects Who Cannot Be Consoled: The Discarded Opening of Albert Angelo and the Queer Afterlife of “BS” Johnson in We Are Made of Diamond Stuff by Isabel Waidner - Chris Clarke (Angles)
In the discarded opening section of Albert Angelo (1964), recovered by Jonathan Coe in his biography of B. S. Johnson, the narrator laments how “God had made another ballsup”: the protagonist’s “other half” is “almost a man instead of wholly a woman”. This essay reads Johnson’s abandoned representation of same-sex desire through the “tradition of queer backwardness” traced by Heather Love in Feeling Backward: Loss and the Politics of Queer History (2007). I argue that the abandoned fragment’s representation of “an unspeakable, inexplicable knowing” between two characters evokes the “backward feelings” which Love proposes are tied to “the historical ‘impossibility’ of same-sex desire” (Love 2007). In doing so, I show how Johnson’s literary afterlife lies in orientating readers to modernity’s denigrated “others”, such as sexual deviants marginalized for refusing to take what Johnson calls the “normal way”. Where the backward feelings in Johnson’s experimental novel illuminate his work’s resistance to various conditions of modern subjecthood, they can equally help us understand the resonance between his work and recent innovative fiction, which also contests punitive forms of social normalization. Isabel Waidner’s “critically British novel”, We Are Made of Diamond Stuff (2019), for example, reanimates Johnson’s perverse character “House Mother Normal” to propel its critique of the inequities of class, queerness, and national identity. We can appreciate what remains most subversive about Johnson’s experimental novels by charting how their backwardness reverberates with the concerns of queer experimental literature in the present.